2003
DOI: 10.1023/a:1027376318530
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Biodegradation of petroleum hydrocarbon contamination is a common method for remediating soils and groundwater. Due to complexities with field-scale studies, biodegradation rates are typically evaluated at the bench-scale in laboratory studies. However, important field conditions can be difficult to mimic in the laboratory. This study investigates three scaling factors that can impact laboratory biodegradation rates and that are frequently unaccounted for in typical laboratory experimental procedures. These fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Excess moisture may also impede bioremediation by saturating soil, reducing the capacity of O 2 to dissolve into the water. This causes aerobic soils to become anaerobic [50]. Lahel et al observed >20% decrease in remediation efficiency of diesel when moisture was increased from 10% to 30% in a series of microcosm experiments [51].…”
Section: Physiochemical Factors Affecting Natural Attenuation Of Pmentioning
confidence: 99%
“…Excess moisture may also impede bioremediation by saturating soil, reducing the capacity of O 2 to dissolve into the water. This causes aerobic soils to become anaerobic [50]. Lahel et al observed >20% decrease in remediation efficiency of diesel when moisture was increased from 10% to 30% in a series of microcosm experiments [51].…”
Section: Physiochemical Factors Affecting Natural Attenuation Of Pmentioning
confidence: 99%
“…Consequently, it will be challenging to obtain biodegradation rates from the site and relying on literature values may be necessary. However, reaction rates obtained under laboratory conditions are not directly applicable on a field scale and rates can vary between sites and change over time [69,78]. As such, incorporating parameters such as biodegradation rates and electron acceptor consumption, presents significant challenges in the modeling process.…”
Section: Challenges In Reactive Transport Modellingmentioning
confidence: 99%